Development of Microstrip Antenna Sensor for Concrete - Mat Yassin, Mohd Razali (2001)
The microwave reflection type sensor using microstrip disk antenna is developed. The purpose of developing the sensor is to monitor the fresh concrete hardening and to determine concrete curing point. The structure of microstrip disk antenna is divided into three parts i.e. radiation surface, substrate and ground plane. This antenna is developed from polytetra fluoroethlene (PTFE) or random micro fibre glass substrate (RTD 5880) with dielectric constant &r = 2.2. The RTD 5880 substrate is selected based on its suitability to operate at the resonant frequency of 10.7 GHz. In developing the microstrip antenna, parameters such as radius of disk, resonant frequency, resistance at resonance, total quality factor, efficiency and bandwidth has to be taken into consideration. The difference between calculation and experimental results of the resonant frequency and resistance at resonance is about 5%. The measurements on fresh concrete and concrete curmg are done in via two techniques namely contact and non-contact. The samples were prepared based on water to cement ratio 0.5, 0.55 and 0.6. These samples are left to dry in natural condition and at room temperature for 1, 3, 7, 14 and 28 days. The results of both techniques showed that reflection from non-contact technique have readings higher than 100 mW and was more stable compared to contact technique. The non-touching technique was also easy to manage when applied to fresh concrete compared to the touching technique. Studies had shown that the power reflection is inversely proportional with concrete curing time. Significant power reflection reduction had occurred during the first three days of curing process. This phenomena was due to accelerated hydration process that happening inside the concrete during that period. As the curing process resumed, hydration process slowed down then reaching approximately a constant rate. It is during this period that the concrete had hardened and gained its strength. Realising the relationship between microwave, moisture content inside the concrete and concrete strength, the microwave moisture sensor is developed to measure the water or moisture content. This approach can be utilized as a technique in non-destructive testing for concrete to monitor concrete hardening process and predict the anticipated concrete strength in order to fulfill design requirements